Comparative Study of Regulatory T Cell Function of Human CD25+CD4+ T Cells from Thymocytes, Cord Blood, and Adult Peripheral Blood. (13th July 2008) - Fujimaki, Wakae; Takahashi, Nozomu; Ohnuma, Kei; Nagatsu, Masayoshi; Kurosawa, Hiromi; Yoshida, Satoko; Dang, Nam H.; Uchiyama, Takehiko; Morimoto, Chikao
Abstract : CD25 + CD4 + regulatory T cells suppress T cell activation and regulate multiple immune reactions in in vitro and in vivo studies. To define the regulatory function of humanCD25 + CD4 + T cells at various stages of maturity, we investigated in detail the functional differences ofCD25 + CD4 + T cells from thymocytes, cord blood (CB), and adult peripheral blood (APB). CBCD25 + CD4 + T cells displayed low-FOXP3 protein expression level and had no suppressive activity. In contrast, CD25 + CD4 + T cells from thymocytes or APB expressed high expression level of FOXP3 protein associated with significant suppressive activity. Although CBCD25 + CD4 + T cells exhibited no suppressive activity, striking suppressive activity was observed following expansion in culture associated with increased FOXP3 expression and a shift from theCD45RA + to theCD45RA − phenotype. These functional differences inCD25 + CD4 + T cells from Thy, CB, and APB hence suggest a pathway of maturation for Treg in the peripheral immune system.